2020
DOI: 10.1021/acs.iecr.0c02836
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Interfacial Interaction to Fabricate Poly(vinylidene fluoride) Composites with High Thermal Conductivity for Heat Exchangers

Abstract: The high interfacial thermal resistance, poor dispersion, and insufficient contact of the fillers in polymer-based composites result in a lower thermal conductivity, restricting the development of heat conduction and dissipation industrial application. In this paper, bioinspired modification of poly­(dopamine) (PDA) was applied to improve the interfacial adhesion performance of copper nanospheres (Cu) and carbon nanotubes (CNTs) in a poly­(vinylidene fluoride) (PVDF) matrix. The synergistic effect of Cu and CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In recent years, the production of hybrid fillers by combining ceramic fillers and metal particles has become a reliable way to obtain polymeric composites with high λ values and excellent insulation at a low filler loading 14,19 . Zhao et al 20 constructed a continuous heat conduction path in polydimethylsiloxane (PDMS) matrix by adding a Cu and Ag layer functionalized Al 2 O 3 ‐based hybrid particles (denoted as Al 2 O 3 ‐Cu‐Ag).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the production of hybrid fillers by combining ceramic fillers and metal particles has become a reliable way to obtain polymeric composites with high λ values and excellent insulation at a low filler loading 14,19 . Zhao et al 20 constructed a continuous heat conduction path in polydimethylsiloxane (PDMS) matrix by adding a Cu and Ag layer functionalized Al 2 O 3 ‐based hybrid particles (denoted as Al 2 O 3 ‐Cu‐Ag).…”
Section: Introductionmentioning
confidence: 99%
“…18 In recent years, the production of hybrid fillers by combining ceramic fillers and metal particles has become a reliable way to obtain polymeric composites with high λ values and excellent insulation at a low filler loading. 14,19 Zhao et al 20 Cu-Ag particles reached a value of 1.4650 W/(mK), which was 651% higher than pure PDMS (0.1950 W/(mK)). Additionally, the AC conductivity of the PDMS composites was less than 10 À10 S/cm, showing good insulation.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…[23][24][25] DA can form a poly(dopamine) (PDA), and its modification enhances hydrogen bond interactions between the nanofiller and the polymeric matrix, thus improving the dispersion of the nanofiller. [26][27][28] Furthermore, it is wellknown that PDA coatings including catechol and ethylamino functional groups offer a valid method to strengthen the compatibility and the interfacial interaction between the nanofiller and matrix. 29 Up to now, in addition to surface modification ways, recent studies have demonstrated that one-dimensional (1-D) CNT could overcome dispersion problem by inhibiting the aggregation of GNP, forming effective 3-D conductive networks.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bridging technique has been used to modify the filler/filler or filler/polymer interfaces. [20][21][22][23][24][25] "Soft" blocks such as 0D nanoparticles, 22,[26][27][28][29] 1D nanotubes/nanowires/whisker [30][31][32][33][34][35][36] and 2D nanosheets, 23,[37][38][39] are employed to bridge "hard" heat fillers at filler/filler interfaces. ITR can be effectively reduced due to the thermal bridging of the fillers.…”
Section: Introductionmentioning
confidence: 99%